Synthesis and Characterizations of Strontium Cerium Oxide Phosphor - Zambare, Pradip; Girase, K. D.; Mahajan, O. H. (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
A new Strontium Cerium Oxide (Sr4Ce2O7) blue phosphor with, orthorhombic structure was synthesized via standard solid state reaction method using strontium oxide and cerium oxide as a raw materials. The samples were characterized by Thermo analytical techniques (TG, DTA, and DTG), Fourier transformation infrared (FTIR) spectroscopy, Raman spectroscopy, and Photoluminescence studies at room temperature. In excitation spectra two excitation bands were located at 361 and 391 nm respectively. The emission spectrum was a broad band peaking at 474 nm, which was suitable for the doping of rare earth ions.